Status of universal drug susceptibility testing in pulmonary tuberculosis patients initiated on treatment in an Urban setting, South India - Banurekha Velayutham; Lavanya Jayabal; Basilea Watson; Saraswathy Jagadeesan; Chandra Suresh; Dina Nair; Radha Gopalaswamy; Bella Devaleenal; Sriram Selvaraju; Chandrasekaran Padmapriyadarsini (Wolters Kluwer Medknow Publications, 2023)
Introduction: Early initiation of drug susceptibility testing (DST) guided anti-tuberculosis treatment benefits the patient in terms of better treatment outcomes and possibly reduces the transmission of tuberculosis (TB) disease in the community. To determine the status of universal DST (UDST) coverage in smear-positive pulmonary TB patients (PTB) initiated on treatment under the TB program in Greater Chennai Corporation. In addition, the barriers and facilitators for UDST were explored. Material and Methods: The data of PTB patients who were initiated on anti-TB treatment from July to December 2019 was abstracted from the NI-KSHAY database of TB Program. The barriers and facilitators for UDST were explored in 5 focus group discussions (FGDs) among the TB program healthcare workers (HCW). UDST coverage was based on the availability of Cartridge-based Nucleic Acid Amplification test (CBNAAT) results in the NI-KSHAY database. Results: The CBNAAT result was available for 1628 (82.6%) of the 1970 smear-positive PTB patients. Non-availability of CBNAAT results was significantly higher among the older age group (>50 years), in female PTB patients, and the Private Sector. Issues with sputum collection, transport of specimens, and receipt of results were highlighted by the HCWs for the non-availability of UDST results. Conclusion: Universal DST coverage in smear-positive PTB patients initiated on treatment in 2019 in Chennai was optimal as per National Strategic Plan for TB elimination UDST target of 80% for the year 2020 but with scope for improvement. The low UDST coverage in the private sector, among female patients and older age groups, needs to be addressed.